Editorial Foreword - Anthony Giddens (Center for Southeast Asian Social Studies (CESASS), 2019)
First of all, to begin with I would like to say how much I support this initiative to promote social science. This special issue of IKAT: the Indonesian Journal of Southeast Asian Studies is originated from the symposium held in September where I delivered my recorded speech through online media in September 4th, 2018. We should highlight that the social science is very crucial to understanding the contemporary world, therefore of core important to the trajectory of any country today. The social sciences were born out of transformation in the 17, 18, 19thcenturies in the west of course), firstly the origin of modern states and origin of politics, then the industrial revolutions, then the origin of economics, and in the 19thcentury, those things becoming more widespread to the world that create Sociology and Anthropology.